Understanding the structure of musical compositions: Is visualization an effective approach?. (April 2017) - De Prisco, Roberto; Malandrino, Delfina; Pirozzi, Donato; Zaccagnino, Gianluca; Zaccagnino, Rocco
Experienced musicians have the ability to understand the structural elements of music compositions. Such an ability is built over time through the study of music theory, the understanding of rules that guide the composition of music, and countless hours of practice. The learning process is hard, especially for classical music, where the rigidity of the music structures and styles requires great effort to understand, assimilate, and then master the learned notions. In particular, we focused our attention on a specific type of music compositions, namely, music in chorale style (four-voice music). Composing such type of music is often perceived as a difficult task because of the rules the composer has to adhere to. In this article, we propose a visualization technique that can help people lacking a strong knowledge of music theory. The technique exploits graphic elements to draw the attention on the possible errors in the composition. We then developed an interactive system, named VisualMelody, that employs the proposed visualization technique to facilitate the understanding of the structure of music compositions. The aim is to allow people to make four-voice music composition in a quick and effective way, that is, avoiding errors, as dictated by classical music theory rules. We have involved 40 people in testing VisualMelody in order to analyze its effectiveness, its usability, and the overall user satisfaction. We partitioned the people involved in the evaluation study into two groups evenly splitting the musical expertise. Then, we had one group use VisualMelody without the visualization facilities and the other using the tool enhanced with our visualization. On average, people in the group that used our visualization were 60% faster and produced music with less errors.